Mitigasi Banjir ROB Perspektif Ecopreneur Muslim - Muh Izza (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
Purpose of this research is to explore the effectiveness of Muslim ecopreneur-based ROB flood mitigation in Pekalongan sub-district, north of Pekalongan city. Environmental based mitigation is very urgent because the environment is a vital element of life. The object of this research is small, medium and large entrepreneurs in 7 villages. This study uses the Community Base Research (CBR) approach through qualitative descriptive analysis by sampling 42 Muslim entrepreneurs. The results of the study show that ROB flood mitigation in North Pekalongan District of Pekalongan City through 3 mechanisms, namely (1) survival mitigation, by renovating buildings ( 2) relocation mitigation, for entrepreneurs who don't need adaptation and (3) balance mitigation, by reducing their business activities because there are business concerns. The effectiveness of ecopreneur-based ROB flood mitigation in North Pekalongan District through 2 mechanisms, (1) structural mechanism, by engineering bureaucratic basis technicians (2) non-structural mechanism by making a regulation, regulation or policy.